Social Reform in Colonial Bengal: Revisiting Vidyasagar - Zafar, Manmay (Philosophy and Progress, 2016)
This paper looks at Vidyasagars programme for widow marriage while also discussing his campaign against Kulin Brahmin polygamy, child marriage and prostitution some of the evils that plagued nineteenth-century Bengali society. Vidyasagars diligent effort for the legalisation of widow marriage ultimately paid off in 1856 as the British colonial administrators drafted widow marriage into law. The two tracts that Vidyasagar published in 1856 in favour of widow marriage have been looked into some detail as well as opposition to his programme from none other than Bankimchandra Chattopadhyay, arguably the greatest Bengali novelist till date. Statistically speaking, not many widows married under the Hindu Widows Remarriage Act, making the Act, according to some critics, almost a dead letter. However, whether statistics alone does justice to the long-term impact Vidyasagars movement has had on Bengals social and intellectual life is also discussed. Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014